2004
DOI: 10.1128/aac.48.5.1756-1762.2004
|View full text |Cite
|
Sign up to set email alerts
|

Dose-Dependent Pharmacokinetics of Itraconazole after Intravenous or Oral Administration to Rats: Intestinal First-Pass Effect

Abstract: The dose-dependent pharmacokinetics of itraconazole after intravenous (10, 20, or 30 mg/kg) and oral (10, 30, or 50 mg/kg) administration and the first-pass effects of itraconazole after intravenous, intraportal, intragastric, and intraduodenal administration at a dose of 10 mg/kg were evaluated in rats. After intravenous administration at a dose of 30 mg/kg, the area under the plasma concentration-time curve from time zero to infinity (AUC 0-ؕ ) was significantly greater than those at 10 and 20 mg/kg (1,090, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
53
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 46 publications
(56 citation statements)
references
References 27 publications
2
53
1
Order By: Relevance
“…The AUC of ITZ after intragastric and intraduodenal administration was significantly smaller compared with intraportal administration, suggesting substantial intestinal first-pass metabolism of ITZ in rats. However, Shin et al (2004) found that the plasma concentration time course of ITZ following a 30-min intraportal infusion of 10 mg/kg was similar to that seen after intravenous infusion suggesting little, if any, hepatic firstpass metabolism of ITZ. This stands in marked contrast to the results of Yoo et al and to our results and may be attributable to the nonphysiologic conditions that were present in the studies by Shin et FIG.…”
Section: First-pass Formation Of Oh-itraconazole and Cyp3a Inhibitionmentioning
confidence: 97%
See 4 more Smart Citations
“…The AUC of ITZ after intragastric and intraduodenal administration was significantly smaller compared with intraportal administration, suggesting substantial intestinal first-pass metabolism of ITZ in rats. However, Shin et al (2004) found that the plasma concentration time course of ITZ following a 30-min intraportal infusion of 10 mg/kg was similar to that seen after intravenous infusion suggesting little, if any, hepatic firstpass metabolism of ITZ. This stands in marked contrast to the results of Yoo et al and to our results and may be attributable to the nonphysiologic conditions that were present in the studies by Shin et FIG.…”
Section: First-pass Formation Of Oh-itraconazole and Cyp3a Inhibitionmentioning
confidence: 97%
“…Dose-dependent pharmacokinetics of ITZ have been described in both rats (Yoo et al, 2000;Shin et al, 2004) and humans (Heykants et al, 1989;Templeton et al, 2008). The concentration-and timedependent clearance and bioavailability of ITZ has been attributed to the inhibition of CYP3A by ITZ and the metabolites that are sequentially formed by CYP3A (Isoherranen et al, 2004;Templeton et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations